Organization of Extracurricular Research Activities of Students while Studying the Subjects of the Natural Science - Mariia Kryva (Pedagogical Discourse, 2015)
The article highlights the actual problem of implementing students’ extracurricular research activity during the natural sciences study. On the basis of theoretical and empirical research the potential of extracurricular research in the formation of an active, creative, self-motivated student’s personality is accentuated. The key characteristics of the basic forms and methods of organizing the extracurricular activities are formulated. The emphasis is placed on the specific examples of organizing the students’ research activity during natural history, biology, geography, physics and chemistry study. The main directions of the work of Students’ Scientific Society within the student government are studied.